2018
DOI: 10.1051/sicotj/2018001
|View full text |Cite|
|
Sign up to set email alerts
|

Early results of total hip arthroplasty using dual-mobility cup in patients with osteonecrosis of the femoral head

Abstract: Introduction: Osteonecrosis of the femoral head (ONFH) remains a therapeutic challenge for patients undergoing total hip arthroplasty (THA). The majority of these patients are young with high functional demand, and show an increased risk of dislocation following surgery than patients with osteoarthritis. The use of double mobility cup (DMC) has been linked with lower rates of complications when compared to conservative cups; however, the literature is scarce over DMC results in patients with ONFH. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Moreover, THA with standard cups following ONFH or FNF has been associated with higher risk of dislocation. 57,10,11,15 Again our results were congruent with those reporting the use of DMC; 3 studies on ONFH reported nil dislocation, 20,23,30 and 4 studies on FNF reported a dislocation rate of no more than 2%. 22,24,31,32 Only Nich et al 33 reported a dislocation rate of 6.6% for FNF; however, all were related to technical errors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, THA with standard cups following ONFH or FNF has been associated with higher risk of dislocation. 57,10,11,15 Again our results were congruent with those reporting the use of DMC; 3 studies on ONFH reported nil dislocation, 20,23,30 and 4 studies on FNF reported a dislocation rate of no more than 2%. 22,24,31,32 Only Nich et al 33 reported a dislocation rate of 6.6% for FNF; however, all were related to technical errors.…”
Section: Discussionsupporting
confidence: 89%
“…16,17 Recently, multiple reports on second and contemporary generations of DMC have demonstrated excellent results when used in high risk patients. [18][19][20][21][22][23][24] Most of these reports conveyed the results from populations having a single at-risk aetiology. The aim of this study is to report and to compare the outcomes of a series of patients having 1 or several combined risk factors for dislocation, treated by THA with DMC.…”
Section: Introductionmentioning
confidence: 99%
“…However, we were concerned about post-operative dislocation. Considering the presence of some acetabular damage during the pre-operative examination and intraoperative findings, THA using the dual mobility system with substantial resistance to dislocation was indicated [ 7 , 8 ]. During the post-operative THA evaluation, the cup inclination angle was 28°, which was rather low, but the combined anteversion angle was within the optimum range [ 9 ] of 57°.…”
Section: Discussionmentioning
confidence: 99%
“…41 A separate review by Assi et al corroborated these findings, with no dislocations and 100% implant survival at 4.25-year follow-up. 42…”
Section: Avascular Necrosis Of the Femoral Headmentioning
confidence: 99%